2018
DOI: 10.1590/0034-737x201865020006
|View full text |Cite
|
Sign up to set email alerts
|

Development, production, and quality of ‘Chonto’ type tomato grafted on cherry tomato introductions

Abstract: Atualmente, o tomate é uma das culturas mais cultivadas no mundo, com o maior valor econômico, aumentando sua demanda e, assim, sua expansão, produção e comercialização. A cultura do tomate é suscetível ao ataque de patógenos com consequências devastadoras no declínio da produtividade de 50 para 100%. Por esta razão, novos métodos de produção são propostos, como o uso de porta-enxertos selvagens, que possuem alta variabilidade genética e genes responsáveis pela resistência a fungos, bactérias, vírus e nematoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(11 reference statements)
2
2
0
Order By: Relevance
“…Similar effects of rootstock on cherry tomato fruit SSC and TA were also reported by Abu Glion et al 11 . Franco et al 39 . reported that rootstocks increased cherry tomato fruit SSC relative to the non‐grafted control.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar effects of rootstock on cherry tomato fruit SSC and TA were also reported by Abu Glion et al 11 . Franco et al 39 . reported that rootstocks increased cherry tomato fruit SSC relative to the non‐grafted control.…”
Section: Discussionsupporting
confidence: 81%
“…12,37 However, Albino et al 9 demonstrated that grafting cherry tomato with interspecific rootstocks (S. lycopersicum × S. habrochaites) resulted in similar SSC, TA, SSC/TA, and pH as the non-grafted cherry tomato. Similar effects of rootstock on cherry tomato fruit SSC and TA were also reported by Abu Glion et al 11 Franco et al 39 reported that rootstocks increased cherry tomato fruit SSC relative to the non-grafted control. Rootstock effects on tomato fruit SSC, TA, SSC/TA, and pH should be more systematically examined and categorized by grafting with different scions and under different growing conditions in future studies.…”
Section: Discussionsupporting
confidence: 80%
“…The larger diameter of the stem below the grafting point found in the rootstock P. aduncum is also the only material whose diameter below the grafting point was greater than the diameter above the grafting pointmay be indicative of incompatibility. However, according to Franco et al (2018), the larger diameter in the rootstock than in the graft is desirable because it raises the pressure, which results in rapid distribution of the solutes throughout the plant structure. An interesting fact observed is that there was a greater depletion of TSS in the stem above the grafting point and a reduction of RS in the stem below and in the roots, indicating that the carbohydrates were being directed to other organs, such as the growth in diameter of the stem and shoots of the rootstock (Ferriani & Krinski, 2019), considering that it was the species whose shoots were more intense.…”
Section: Discussionmentioning
confidence: 99%
“…Cherry tomato ( Lycopersicon esculentum Mill.) is a worldwide‐cultivated vegetable and is favorably received by consumers for its high nutritional value and pleasant taste 1 . However, tomato crops are vulnerable to various diseases, from the field through to postharvest handling, of which gray mold is the most common one 2 .…”
Section: Introductionmentioning
confidence: 99%